A case study on integrating anaerobic digestion into agricultural activities in British Columbia: Environmental, economic and policy analysis. (15th February 2021) - Wang, Haoqi; Bi, Xiaotao; Clift, Roland
Abstract: This paper provides an example of the kind of analysis needed to support better targeted policies to reduce the environmental impacts of agricultural activities, using the specific case of Anaerobic Digestion (AD) to treat animal manure and other agricultural and food wastes in British Columbia (BC). Economic and life cycle environmental performance metrics are estimated to compare integrated and stand-alone systems using the resulting biogas and digestate. Using biogas for heating outperforms purifying it for distribution as renewable natural gas (RNG). However, current policy and energy prices in BC perversely support RNG, making biogas-fired heating systems economically unattractive. The performance of biogas-fired heating system can be improved and their dependence on subsidies reduced by integration with local agricultural activities, exploiting CO2 and digestate as by-products. Biogenic CO2, from combustion of the biogas and from mushroom cultivation, can displace natural gas use in producing CO2 -enriched atmospheres to enhance growth rates in greenhouse production. Using digestate as growing media in greenhouses and mushroom cultivation can generate significant revenues but the environmental benefits are nugatory. Co-digestion of food waste can further improve performance by increasing biogas yield. With all extra benefits combined, integrated AD systems can increase both GHG mitigation and revenues by at least 80%. The analysis illustrates the general point that, to avoid perverse outcomes, policy measures must support options based on their actual GHG mitigation benefits, rather than targetting any specific technology. Graphical abstract: Image 1 Highlights: Biogas heating has higher GHG mitigation at lower cost than CHP or RNG. Stand-alone biogas options require financial support from policy measures in BC. Integrating AD into a broader system achieves further GHG and economic benefits. Policy measures need to be supported by such systematic analyses. Abstract : Integration of anaerobic digestion with agricultural activities can further reduce energy and material consumption and achieve substantial environmental and economic benefits from stand-alone biogas options.